PROTOCOL: The impact of agricultural mechanisation on women's economic empowerment: A mixed‐methods systematic review - Masset, Edoardo; Kapoor Malhotra, Suchi; Gupta, Neha; Bhandari, Ratika; White, Howard; MacDonald, Heather; Puskur, Ranjitha; Singaraju, Niyati; Sharma Waddington, Hugh (Wiley, 2023)
This is the protocol for a Campbell systematic review. The main objective of the review is to answer the following questions: What is the impact of mechanisation on agriculture? What is the impact of mechanisation on women's economic empowerment? The study will review the impact of mechanisation on labour demand and supply, land and labour productivity, farmers' incomes, health and women's empowerment. All literature will be considered, including nonintervention studies and studies not reporting gender‐disaggregated results.